Maranao oral literature in search of historical sources - Tawagon, Manuel R. (2017)
This modest paper attempts to show that Maranao oral literature is indeed a source of historical data and information. Maranao oral literature not only serves as a vehicle of history but also reflects the culture of the people and their institutions. It is their own ethnography which gives a penetrating picture of their way of life. To understand the Maranaos is to understand their literature. Dealing with them also necessitates a knowledge of their literature which embodies their laws, norms and conduct, behavior, origins, beliefs, practices, and rituals. It is the basic reference to explain events and other social and political activities which are believed to be the legacies of the past. In other words, the oral literature of the Maranaos is the basis of any attempt to reconstruct their history, culture, and society because all things Maranao come real deep from that literature.
Keywords: Folk literature, Philippine; Maranao ( Philippine people) -- Folklore; Darangen (Maranao epic)